REVIEWING THE POTENTIAL AND RISKS OF ADRO SHARES AS AN INVESTMENT ON THE INDONESIA STOCK EXCHANGE - Riska Intan Pramitaningtyas; Suparta, Virgi Ainun Iqba; Suparta, Achmad Reza; Suparta, AlvineWijaya Un; Suparta, I Made (Nirta Learning Centre, 2025)
The coal mining industry plays a vital role in the Indonesian economy, providing energy for power plants and raw materials for the cement, steel and chemical industries. The financial performance of coal companies is important to investors, creditors and the government, who require accurate assessments for decision-making.This study aims to examine the potential and risk of PT Adaro Energy Indonesia Tbk (ADRO) shares as an alternative investment on the Indonesia Stock Exchange (IDX). ADRO is an integrated energy company engaged in the coal mining sector and has a significant contribution in providing national energy and exports.The method used in this study is descriptive qualitative with a literature study approach and secondary data analysis obtained from the company's financial statements, stock price movements, and coal commodity market trends. Investors need to consider fundamental, technical, and external dynamics aspects before making investment decisions on ADRO shares.